PERATAAN LABA DITINJAU DARI CASH HOLDING, PROFITABILITAS DAN UKURAN PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA: INCOME SMOOTHING: REVIEW FOR CASH HOLDING, PROFITABILIT,Y AND COMPANY SIZE IN MANUFACTURING COMPANY IN INDONESIA - Asri, Fatjhar; Fauziati, Popi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
The purpose of this research is to look into the impact of cash holding, profitability, and business size on income smoothing subject of this study is a manufacturing business listed on the Indonesia Stock Exchange in the products and consumption sub-sector. Purposive sampling was utilized to collect data. data-binarygistic regression is the data analysis strategy used to confirm the hypothesis is correct. The SPSS application is used to process the information. Cash holding2has a substantial2effect on income smoothing, but profitability and company size has no significant effect on income smoothing in manufacturing and consumption sub-sector companies on the Indonesia Stock Exchange, according to the results of hypothesis testing.